Impact of baseline microbiological status on clinical outcomes in generalized aggressive periodontitis patients treated with or without adjunctive amoxicillin and metronidazole: an exploratory analysis from a randomized controlled clinical trial. (11th September 2014) - Guerrero, Adrián; Nibali, Luigi; Lambertenghi, Roberta; Ready, Derren; Suvan, Jean; Griffiths, Gareth S.; Wilson, Michael; Tonetti, Maurizio S.
Abstract Aim To explore whether subjects harbouring A. actinomycetemcomitans, P. gingivalis or T. forsythia at baseline showed increased clinical benefits with the adjunctive use of systemic amoxicillin and metronidazole (AMX‐MET) during non‐surgical treatment of generalized aggressive periodontitis (GAgP). Material and Methods Forty one subjects were included in this 6‐month randomized placebo‐controlled clinical trial using a 7‐day course of systemic AMX‐MET or placebo as adjuncts to non‐surgical periodontal therapy. Clinical and microbiological parameters were collected at baseline, 2 and 6 months after treatment. Microbiological cultures were processed for pooled subgingival samples and identities of isolates were determined by PCR for A. actinomycetemcomitans, P. gingivalis and T. forsythia Results At 6 months, the test treatment resulted in significant additional improvements in the primary outcome variable compared to placebo, and the effect of the adjunctive antimicrobials was not modified by the baseline microbiological status in the primary analysis. However, secondary exploratory subgroup analyses showed improved clinical outcomes in subjects harbouring A. actinomycetemcomitans at baseline compared to subjects who did not harbour this pathogen. Conclusions All subjects benefited from the tested adjunctive antimicrobial regimen, although subjects who harboured A. actinomycetemcomitans at baseline may show greater clinical benefits. Larger appropriately powered studies are needed to confirm whether adjunctive AMX‐MET is more beneficial for GAgP patients who harbour A. actinomycetemcomitans, along with other key periodontal pathogens.